CLINICAL AND EPIDEMIOLOGICAL PROFILE OF HIV-INFECTED PREGNANT IN THE SANTA CASA DE MISERICORDIA OF ANÁPOLIS, GOIÁS (CIPEEX, 2022)
THE ACQUIRED IMMUNODEFICIENCY SYNDROME (AIDS) IS ONE OF THE LEADING EPIDEMICS IN THE WORLD, CHARACTERIZED BY IMMUNE SYSTEM DYSFUNCTION CAUSED BY THE HUMAN IMMUNODEFICIENCY VIRUS (HIV). THE MALE SEX STILL REPRESENTS THE LARGEST NUMBER OF CASES, BUT THE INCIDENCE AND PREVALENCE IN WOMEN HAS BEEN INCREASING, BEING NOW ALMOST HALF OF THE OCCURRENCES. ONE OF THE AGGRAVATING FACTORS OF THE CONTAMINATION AMONG THE FEMALE PUBLIC IS THE GESTATIONAL PERIOD, DUE TO THE CHANCES OF VERTICAL TRANSMISSION. THEREFORE, THE OBJECTIVE OF THIS STUDY IS TO VERIFY THE CLINICAL AND EPIDEMIOLOGICAL PROFILE OF HIV POSITIVE PREGNANT WOMEN IN THE SANTA CASA DE MISERICÓRDIA HOSPITAL IN ANÁPOLIS, GOIS. THIS IS AN EPIDEMIOLOGICAL, ANALYTICAL AND RETROSPECTIVE STUDY OF HIV POSITIVE PREGNANT WOMEN ATTENDED AT SANTA CASA DE MISERICÓRDIA HOSPITAL OF ANÁPOLIS, GOIS FROM JANUARY 2013 TO JANUARY 2018. DATA COLLECTION WILL BE PERFORMED BASED ON MEDICAL RECORDS ANALYSIS. INCLUSION CRITERIA ARE PREGNANT WOMEN WHO HAD AT LEAST TWO PRENATAL CONSULTATIONS AND THE EXCLUSION CRITERIA ARE INCOMPLETE MEDICAL RECORDS. IT IS HOPED TO DESCRIBE THE CLINICAL CHARACTERISTICS AND THE EPIDEMIOLOGICAL PROFILE OF THESE PREGNANT WOMEN, SO THAT THE DATA COLLECTED BECOME OF GREAT VALUE AND SERVE AS A SUBSIDY FOR FUTURE PLANNING OF CARE AND FOCUSED ACTIONS TO THIS POPULATION, REDUCING THE RISKS OF MOTHER-TO-CHILD TRANSMISSION AND CONSEQUENTLY UNFAVORABLE POSTNATAL OUTCOMES INVOLVING EXPOSED CHILDREN.
Keywords: HIV seroprevalence. Vertical transmission. Prenatal. Women's health.